THE INFLUENCES OF ACCOUNTABILITY, TRANSPARENCY AND INTERNAL CONTROL WITH PARTICIPATION AS MODERATION VARIABLE ON FRAUD PREVENTION IN VILLAGE FUNDS MANAGEMENT - Annisa Febriarty; M.Th. Heni Widyarti; I Nyoman Romangsi (Politeknik Negeri Semarang, 2022)
This study aimed to analyze the influences of accountability, transparency, and internal control with participation as moderation variables on fraud prevention in village funds management. Primary and secondary data were collected by questionnaire and interview. The objects are five villages of Pabelan District, Semarang Regency namely, Bendungan, Karanggondang, Kadirejo, Terban, and Semowo. Sampling method used purposive sampling. The number of samples is 102 respondents of Village Officials, Badan Permusyawaratan Desa (BPD), and the Farmers Group (Kelompok Tani & Kelompok Wanita Tani). This study used IBM SPSS version 22 software program. The results of the hypothesis analysis are accountability and internal control partially influences fraud prevention while transparency partially does not influence fraud prevention. Accountability, transparency, and internal control simultaneously influence fraud prevention and participation moderates the influences of accountability, transparency, and internal control simultaneously on fraud prevention in village funds management.